Treatment Outcome of Severe Acute Malnutrition and Its Determinants among Pediatric Patients in West Ethiopia - Muluken Berhanu Mena; Mohammed Gebre Dedefo; Bruke Berhanu Billoro (Hindawi Limited, 2018)
Background. Malnutrition is a silent killer that is underreported, underaddressed, and as a result underprioritized. It is reported that severe acute malnutrition is the commonest reason for pediatrics hospital admission in many poor countries; 25 to 30% of children with severe malnutrition die during hospital admissions. Objective. To determine treatment outcome of severe acute malnutrition and identify its determinants among pediatric patients in pediatrics ward of Nekemte Referral Hospital. Methods. A retrospective hospital-based cross-sectional study was done from November 2015 to April 2017. Data had been collected by using checklist for recording information from patient card and register book. Association between independent variables and depend variable was assessed using bivariate and stepwise multivariable logistic regression, respectively. Level of statistical significance was declared at p value < 0.05. Results. Out of 205 admitted children with severe acute malnutrition, 137 (66.8%) cases were cured from SAM, 9 (4.4%) cases were died because of SAM, and (16.6%) cases were defaulter from SAM management, and 25 (12.2%) cases were transferred out. Multivariable logistic regression showed that children admitted with both edema and wasting AOR = 8.30, 95% CI (1.72, 40.09) P=0.008, children without hypothermia AOR = 2.91, 95%CI (1.10, 7.69) P=0.031, children who stay 8-14 days AOR = 3.86, 95%CI (1.01, 14.75) P=0.048, children without pneumonia AOR = 7.82, 95%CI (2.74, 222.29) P=0.001, children without anemia AOR = 3.22, 95%CI (1.04, 9.97) P=0.042, and children without HIV AOR = 9.21, 95% CI (2.20, 38.54) P=0.002 were more likely to be cured from severe acute malnutrition. Conclusion. Treatment outcome of severe acute malnutrition in this study is good. It shows that around three-fourths of the children were cured. Factors such as admission criteria, hypothermia, length of stay, pneumonia, anemia, and presence of HIV were associated with treatment response.